Developmental Care: assistance of nurses from Neonatal Intensive Care Units - Bruna de Souza Lima Marski; Beatriz Castanheira Facio; Sueli Mutsumi Tsukuda Ichisato; Patricia Carla de Souza Della Barba; Monika Wernet
ABSTRACT Objective: to analyze the Developmental Care in nursing care for Newborns in critical Neonatal Intensive Care Units. Method: a qualitative study with 11 nurses from Neonatal Intensive Care Units of a city in the State of São Paulo countryside, based on the Developmental Care. Data collection was based on non-participant observation, documentary research in medical records and semi-structured interviews. The Symbolic Interactionism was adopted as theoretical framework, and the Bardin Content Analysis, as method of analysis. Results: nurses have knowledge about Developmental Care; however, there are dissonances with doing them. The analysis is presented from two thematic categories: "Nurses' performance in the Developmental Care" and "Nurse, Family and Developmental Care". Final considerations: it is necessary to encourage reflections on the care of nurses regarding Developmental Care, and to foster sensitivity and perception in relation to the executed and registered.